ON THE EVOLUTIONARY STATUS OF LOW-METALLICITY BLUE COMPACT GALAXIES - Pilyugin, L. S. (Одеські астрономічні публікації, 2017)
A remarkably small scatter in the N/O ratios for the HII regions in low-metallicity blue compact galaxies (BCG) has been found recently by Izotov and Thuan. They have concluded that these galaxies are presently undergoing their first burst of star formation, and that nitrogen measured in these galaxies is produced by massive stars in the current star formation burst only. Here it has been tested whether this interpretation is compatible with other observational data and with the existing ideas on the chemical evolution of galaxies. It has been found that the existence of systems (damped L absorbers) in which the N/Si ratios are lower than in low-metallicity BCGs and the chemical homogeneity of star-forming BCGs are in conflict with conclusion that the massive stars from current star formation event are responsible for the nitrogen abundance measured in low-metallicity BCGs. The low-metallicity BCGs seem to be systems with a small amount of old underlying stellar population over which the current star formation burst is superposed; only the stars from the previous star formation event(s) are responsible for the observed chemical composition in the giant HII regions in these galaxies.